Instrumentação de um tribômetro para ensaios de deslizamento em dutos flexíveis - Ladeira, Guênia Mara (2011)
The flexible pipes are used extensively as a means of conducting crude oil, gas and water between the wellheads and oil platform. These pipes are made of layers of polymeric materials, interspersed with steel straps, forming a composite that combines high corrosion resistance and flexibility of movements. They absorb the changes imposed by water currents, but can wear the outer polymeric layer. In order to simulate this tribossistema, the Laboratório de Tecnologia em Atrito e Desgaste designed and built a tribometer able to reproduce middle-scale conditions similar to the wear that occurs on the field. The developed device consists of a system capable of alternating vertical movements in underwater environment, and applied on the samples tested loads normal to its surface, whose values can reach 1000 kN. The automation control and monitoring of process variables is essential for the correct operation of the equipment. In this dissertation is describes the instrumentation developed for this tribometer, with preliminary testing of the sensors and the analysis of mechanical performance and data obtained from the sensors to each subsystem. Finally, after complete assembly and testing of the tribometer, we could verify that the performance of mechanical and instrumentation system oscillation attend the function for which the system was designed. Furthermore, it was observed that the proportional valve control hydraulic pressure of the compression system is inadequate to sample the range of applied forces, and must be replaced. After the tube change the system retested. The force sensors of the compression system are adequate. The sensors, in principle, would measure the wear of the samples showed shifts in the alternation of the direction of movement of the flexible duct, and low resolution. Setting up these sensors will be used only to limit the maximum wear of the samples. The wear characteristics of the samples need to be analyzed out of the tribometer, with more precise tools. Vibration levels for loads tested were too low, not acting for the equipment problem.